Approximate Relativistic Mass-Formulae for the Ground State Binding Energy of a Λ in Hypernuclei - Koutroulos, C. G.; Grypeos, M. E. (HNPS Advances in Nuclear Physics, 2020)
The Dirac equation with potentials having attractive and repulsive parts is con sidered in a simplified model and approximate semiempirical mass formulae for the ground state binding energy of a Λ in hypernuclei are derived and discussed.